1985
DOI: 10.1136/thx.40.11.840
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular triamcinolone acetonide in chronic severe asthma.

Abstract: ABSTRACT, Seventeen subjects with chronic severe asthma completed a 48 week prospective, double blind study with crossover of treatment at 24 weeks, in which triamcinolone acetonide 80 mg intramuscularly every four weeks was compared with oral prednisolone 10 mg daily. Spirometry, twice daily measurements of peak expiratory flow rate, and self assessment of asthma symptom scores showed significant improvement during triamcinolone treatment; less extra prednisolone was required and there was significant weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Although the exact pharmacokinetic potency of triamcinolone versus oral prednisolone is unclear, triamcinolone likely has greater affinity for the glucocorticoid receptor because early studies in adults with severe refractory asthma have shown greater treatment efficacy with a single 80-mg dose of triamcinolone dose than with a 10-mg dose of prednisolone daily. 45,46 The dose of triamcinolone used in this study was based on previous reports of feasibility and efficacy in children with a similar dosing strategy. 47,48 The 2-week time point that was used for outcome assessment was based on previous studies in adults with severe refractory asthma that demonstrated no clinically meaningful differences between 2 versus 4 weeks of triamcinolone treatment 45 and significant improvement in symptoms, lung function, and airway eosinophils (with almost complete eosinophil disappearance) after only 2 weeks postadministration.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pharmacokinetic potency of triamcinolone versus oral prednisolone is unclear, triamcinolone likely has greater affinity for the glucocorticoid receptor because early studies in adults with severe refractory asthma have shown greater treatment efficacy with a single 80-mg dose of triamcinolone dose than with a 10-mg dose of prednisolone daily. 45,46 The dose of triamcinolone used in this study was based on previous reports of feasibility and efficacy in children with a similar dosing strategy. 47,48 The 2-week time point that was used for outcome assessment was based on previous studies in adults with severe refractory asthma that demonstrated no clinically meaningful differences between 2 versus 4 weeks of triamcinolone treatment 45 and significant improvement in symptoms, lung function, and airway eosinophils (with almost complete eosinophil disappearance) after only 2 weeks postadministration.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment in the adrenopituitary axis was noted in 23% of the patients given intramuscular TA and they recovered only 2 months after withdrawal. McLeod et al [27] compared TA 80 mg i.m. every 4 weeks to daily oral prednisone 10 mg in the treatment of asthma.…”
Section: Discussion and Reviewmentioning
confidence: 99%
“…Initial studies that investigated individuals with severe asthma generally considered it to be a lack of effect of oral steroids on symptoms or exacerbation rates , or to the presence of fixed airflow obstruction . Symptoms and a consideration of fixed airflow obstruction also formed the basis of the initial National Asthma Education and Prevention Program (NAEPP) classification of asthma severity .…”
Section: Evolution Of the Definition Of Severe Asthmamentioning
confidence: 99%